2013
DOI: 10.5713/ajas.2012.12504
|View full text |Cite
|
Sign up to set email alerts
|

Diets Based on Sugar Cane Treated with Calcium Oxide for Lambs

Abstract: This experiment was conducted to evaluate the intake, nutrient apparent digestibility and the effect of total collection days (two and four days) on apparent digestibility estimates for lambs fed diets containing sugar cane treated with calcium oxide (CaO). Eight Santa Inês castrated male lambs with a 16.6±1.8 kg body weight were used. The lambs were distributed in two 4×4 Latin squares, with four experimental periods of 14 d each. The animals were kept in 1.2 m2 individual pens, and the intake and digestibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
1
8
0
1
Order By: Relevance
“…Apparent digestibility of OM and CP in cattle fed with SBU was the highest (P < 0.05) among groups while NDF and ADF digestibility was most improved in cattle consumed SBUC as roughage source, followed by SBU, RS, and SB, respectively. According to Khejornsart et al (2011) and Carvalho et al (2013), alkaline treatment could improve digestibility and feed intake of ruminants because it alters the structure of lignin removal from the lignocellulose. Removing lignin from the inner parts of the cell wall consequently resulted in a damage and porous morphology by separation of cell bundles, forming long cellular structures, which are well connected in the longitudinal direction (Rezende et al 2011).…”
Section: The Effect On Feed Intake and Digestibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Apparent digestibility of OM and CP in cattle fed with SBU was the highest (P < 0.05) among groups while NDF and ADF digestibility was most improved in cattle consumed SBUC as roughage source, followed by SBU, RS, and SB, respectively. According to Khejornsart et al (2011) and Carvalho et al (2013), alkaline treatment could improve digestibility and feed intake of ruminants because it alters the structure of lignin removal from the lignocellulose. Removing lignin from the inner parts of the cell wall consequently resulted in a damage and porous morphology by separation of cell bundles, forming long cellular structures, which are well connected in the longitudinal direction (Rezende et al 2011).…”
Section: The Effect On Feed Intake and Digestibilitymentioning
confidence: 99%
“…The concentration of alkaline agents can chemically break the ester bonds between lignin and hemicellulose and cellulose, and physically make structural fibers swollen ) which enable rumen microbes to attack the structural carbohydrates more easily (Castañón-Rodríguez et al 2015). Moreover, Carvalho et al (2013) reported that feeding alkali-treated SB increased feed intake and body weight (BW) of ruminant. However, there are still a limitation data on the use of calcium hydroxide (Ca(OH) 2 ) and/or combination with urea for SB treatment on nutritive quality and the use as roughage source for ruminant feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of calcium oxide (CaO) in the treatment of sugar cane has been reported to maintain the nutritional quality of forage for a few days without the need for daily cuts (Oliveira et al, 2007) and to improve its nutritional value (Pires et al, 2010;Carvalho et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sugarcane is an excellent alternative feed for ruminants during droughts, and although sugarcane is low-quality forage, its use is justified by being an easily implemented perennial crop with high productivity (Carvalho et al 2013).…”
Section: Introductionmentioning
confidence: 99%